Crossing Cultural Boundaries: Saint George in the Eastern Mediterranean under the Latinokratia (13th–14th Centuries) and His Mythification in the Crown of Aragon - Manuel Castiñeiras (Arts, 2020)
The cult of St George in the Eastern Mediterranean is one of the most extraordinary examples of cohabitation among different religious communities. For a long time, Greek Orthodox, Latins, and Muslims shared shrines dedicated to the Cappadocian warrior in very different places. This phenomenon touches on two aspects of the cult—the intercultural and the transcultural—that should be considered separately. My paper mainly focuses on the cross-cultural value of the cult and the iconography of St George in continental and insular Greece during the Latinokratia (13th–14th centuries). In this area, we face the same phenomenon with similar contradictions to those found in Turkey or Palestine, where George was shared by different communities, but could also serve to strengthen the identity of a particular ethnic group. Venetians, Franks, Genoese, Catalans, and Greeks (Ῥωμαῖοι) sought the protection of St George, and in this process, they tried to physically or figuratively appropriate his image. However, in order to gain a better understanding of the peculiar situation in Frankish-Palaiologian Greece, it is necessary first to analyze the use of images of St George by the Palaiologian dynasty (1261–1453). Later, we will consider this in relation to the cult and the depiction of the saint on a series of artworks and monuments in Frankish and Catalan Greece. The latter enables us to more precisely interrogate the significance of the former cult of St George in the Crown of Aragon and assess the consequences of the rulership of Greece for the flourishing of his iconography in Late Gothic art.